Risk of Buruli ulcer and detection of Mycobacterium ulcerans in mosquitoes in southeastern Australia. - Caroline J Lavender; Janet A M Fyfe; Joseph Azuolas; Karen Brown; Rachel N Evans; Lyndon R Ray; Paul D R Johnson (Public Library of Science (PLoS), 2011)
BACKGROUND: Buruli ulcer (BU) is a destructive skin condition caused by infection with the environmental bacterium, Mycobacterium ulcerans. The mode of transmission of M. ulcerans is not completely understood, but several studies have explored the role of biting insects. In this study, we tested for an association between the detection of M. ulcerans in mosquitoes and the risk of BU disease in humans in an endemic area of southeastern Australia. METHODOLOGY/PRINCIPAL FINDINGS: Adult mosquitoes were trapped in seven towns on the Bellarine Peninsula in Victoria, Australia, from December 2004 to December 2009 and screened for M. ulcerans by real-time PCR. The number of laboratory-confirmed cases of BU in permanent residents of these towns diagnosed during the same period was tallied to determine the average cumulative incidence of BU in each location. Pearson's correlation coefficient (r) was calculated for the proportion of M. ulcerans-positive mosquitoes per town correlated with the incidence of BU per town. We found a strong dose-response relationship between the detection of M. ulcerans in mosquitoes and the risk of human disease (r, 0.99; 95% CI, 0.92-0.99; p < 0.001). CONCLUSIONS/SIGNIFICANCE: The results of this study strengthen the hypothesis that mosquitoes are involved in the transmission of M. ulcerans in southeastern Australia. This has implications for the development of intervention strategies to control and prevent BU.